The undue influence of genetic information on senior medical students’ treatment decisions - Andrew Stuart Lane; Kate E. Lynch; Mark Arnold; Ilan Dar-Nimrod; James Morandini; Stefan A. Gawronski; Paul E. Griffiths (BMC Medical Education, 2023)
Abstract Background Knowledge of the genetic basis of health conditions can influence how the public perceives their own and others’ health. When there are known genetic associations for such conditions, genetic essentialist biases facilitate deterministic thinking and an over-emphasis of genetic causality. This study investigates the role that genetic essentialist biases play in medical decision-making. Methods Senior postgraduate medical students (N = 102) read a scenario in which a patient presents with gastroenterological symptoms. Half of the students were told that the patient tested positive for HLADQ2 – a gene implicated in, but not deterministic of, coeliac disease. The other half received no genetic information. Students were assessed on their recommendations for investigation and management using a multiple-choice questionnaire. Twenty-two of these students participated in a qualitative follow-up which used focus groups and semi-structured interviews to explore the reasoning behind students’ responses. Results Management recommendations differed between the two groups, with those receiving genetic information more likely to recommend a gluten free diet. Recommendations for further investigation did not differ significantly between groups. Interviews suggested that these findings arose despite the students’ good understanding of the common non-deterministic nature of genes, such as HLADQ2. Conclusion Differences in management recommendations suggest that the inclusion of genetic information unduly biased students towards a premature diagnosis of a serious health condition, coeliac disease. Follow-up interviews introduced the possibility that observed manipulation-based differences may have been based on anticipated expectations of examiners, rather than perceived future clinical practice. Based on the present results it is unclear whether intentional exam-taking strategies fully account for medical students’ decisions, or if they contribute in addition to the activation of genetic essentialist biases. Further research in clinical settings may ascertain whether genetic essentialist biases would truly influence medical student and doctors within their clinical practice environment.